Detection of Cervical Precancer Using Visual Inspection Method with Acetic Acid - Baral, Gehanath; Oli, Lila; Verma, Sheela; Rai, Snigdha; Aryal, Parshuram; Tiwari, Suman (Journal of Nepal Health Research Council, 2024)
Background: Cervical cancer screening is the priority activity of the government. Visual inspection with Acetic acid (VIA), Pap smear Liquid-based cytology, and HPV DNA testing are different methods of screening. VIA-based screening is the cost-effective method of screening in a resource-constrained setting like in our country as this doesn’t require cyto-histological testing, can be performed by trained paramedics too, and is as accurate as a cytological test. The aim is to explore pre-cancer cervical lesions by screening women in the community by visual inspection using acetic-acid. Methods: Community-based cross-sectional study done at a health camp setting for three months from March to June 2023. The married non-pregnant women of 30-60 years were screened. Descriptive tests as well as sub-group analysis performed by Chi-Square tests. Results: From ten community health camps, 1255 cases were screened and screen positivity was 14.3%. Positive results were proportionately distributed to all parity by 13-19%. Half of the positive results (47.2%) were in the 34-40 age group. There were no significant differences in screen positivity by parity or vaginal discharge. Menopausal women had 7.7% screen positivity. Conclusions: The prevalence of VIA positivity in the community was found double the previous facility-based prevalence; and there was no significant difference by parity, menopausal status, and vaginal discharge. The positivity was more in 30-45 years of age. Keywords: Cervical pre-cancer; screening; VIA.